Attentional-Tracking Acuity Is Modulated by Illusory Changes in Perceived Speed - Marinovic, Welber; Pearce, S.; Arnold, D. (2013)
Many activities, such as driving or playing sports, require simultaneous monitoring of multiple, often moving, objects. Such situations tap people's ability to attend selected objects without tracking them with their eyes-this is known as attentional tracking. It has been established that attentional tracking can be affected by the physical speed of a moving target. In the experiments reported here, we showed that this effect is primarily due to apparent speeds, as opposed to physical speeds. We used sensory adaptation-in this case, prolonged exposure to adapting stimuli moving faster or slower than standard test stimuli-to modulate perceived speed. We found performance decrements and increments for apparently sped and slowed test stimuli when participants attempted attentional tracking. Our data suggest that both perceived speed and the acuity of attention for moving objects reflect a ratio of responses in low-pass and band-pass temporal-frequency channels in human vision.